P0324SODIUM ZIRCONIUM CYCLOSILICATE TO PREVENT HYPERKALAEMIA IF HAEMODIALYSIS IS POSTPONED DUE TO VASCULAR ACCESS COMPLICATIONS: EXPERIENCE FROM CLINICAL PRACTICE. (6th June 2020) - Brooks, Owain; Mikhail, Ashraf; Brown, Chris; Gumbleton, Mark; Jenkins, Justine; Boyle, Kaitlin
Abstract: Background and Aims: Vascular access is a fundamental aspect of haemodialysis (HD) treatment. Vascular access may be compromised due to central venous catheter (CVC) thrombosis, arterio-venous fistula (AVF) or graft (AVG) stenosis, infections or perioperative complications that require urgent resolution or the formation of alternative emergency or definitive access. Sodium zirconium cyclosilicate (SZC) (Lokelma®) is a new oral potassium binder. We offer an insight into SZC treatment to prevent hyperkalaemia in patients where HD is postponed due to vascular access complications. Method: Adult prevalent HD patients were included for analysis. Each patient was unable to receive their full scheduled HD treatment due to a vascular access complication. SZC was prescribed on the day HD was not possible (D1) until the vascular access issue was resolved and HD could recommence. The primary efficacy measures were the prevention of increases in serum potassium (sK + ), the safe postponement of HD and the avoidance of emergency hospital admission. Results: Four patients receiving thrice-weekly HD (mean age 69 years, all male) received SZC for a mean duration of 3.5 days (min 2 days, max 6 days). No patients were admitted during these acute episodes. The mean pre-dialysis sK + on D1 was 6.0mmol/L (K1). No post-dialysis sK + values were obtained on D1 because HD was not possible or cut-short (Table 1). For patients 2 and 3, one and 10 HD treatments preceded the next sK + (K2) respectively. sK + reduced from 5.8mmol/L (K1) to 4.8mmol/L (K2) for patients 1 and 4 (Table 1). No statistical analyses were undertaken due to the low patient numbers. HD was delayed beyond the scheduled treatment date for 3 of the 4 patients, with a mean delay of 1.75 days (min 0 days, max 3 days) (Table 2). There was no delay between HD treatments for patient 2, who only received 1 hour HD treatment on D1. The last full HD treatment for patient 2 was 3 days prior to D1. A gap between SZC initiation (D1) and the next HD treatment was seen for all four patients, with a mean gap of 2 days (min 1 day, max 3 days) (Table 2). Conclusion: Sodium zirconium cyclosilicate can be used to successfully reduce, or avoid an increase in sK + in mild to moderate hyperkalaemia, avoid emergency hospital admission and allow HD to be postponed for a valuable short period until HD vascular access can be re-established.